ASUHAN KEBIDANAN BERKESINAMBUNGAN PADA NY.M DENGAN PENERAPAN AKUPRESURE MASSAGE DI PUSKESMAS MAJALAYA KABUPATEN BANDUNG - Adinda Lutfiah (Jurnal Kesehatan Siliwangi, 2025)
Continuity of midwifery care provides consistent services from pregnancy through the postpartum period and neonatal care, allowing midwives to monitor the mother's condition holistically. One of the main concerns during labor is pain, particularly in the active phase of the first stage due to uterine contractions and cervical dilation. Acupressure massage can be used as a non-pharmacological method to alleviate pain by stimulating specific points that trigger endorphin release. The aim of this report is to describe the implementation of continuity of midwifery care in Ms. M, with the use of acupressure massage as a pain management intervention during labor. This study used a case study design with a midwifery management approach, including assessment, diagnosis, planning, implementation, and evaluation. Acupressure massage was applied at the LI4 and SP6 points during the active phase of the first stage of labor in accordance with established procedures. Pain intensity was measured using the Visual Analog Scale (VAS). The results of the midwifery care implementation showed that during pregnancy, Ms. M experienced weight gain that did not meet the recommended minimum standard. The labor process proceeded physiologically and without complications, with the application of acupressure as a non-pharmacological intervention to help reduce labor pain. The postpartum period progressed normally, although the mother experienced sore nipples, which were managed through breast care education. The newborn’s condition was within normal limits, with no complications observed. The mother was also able to independently provide neonatal care and chose a contraceptive method appropriate to her needs and condition. Acupressure massage proved effective as part of continuity of midwifery care because it is safe, easy to apply, and enhances maternal comfort during labor. Midwives are encouraged to improve accuracy in care provision to prevent gaps between theory and practice and to apply acupressure massage consistently